COVID-19 Extrapulmonary illness - The Impact of COVID-19 on Nephrology care (2020)
Coronavirus disease-2019 (COVID-19) has caused a pandemic that has affected millions of people worldwide. COVID-19 is caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and is spread by close contact and by respiratory droplets. It has also impacted different aspects of caring for people with kidney disease, including those with acute kidney injury (AKI), chronic kidney disease (CKD), those requiring kidney replacement therapy (KRT), and those with a kidney transplant. All of these patients are considered high risk. The lessons learned from the COVID-19 pandemic will hopefully serve to protect patients with kidney disease in a similar situation in the future.